Matéria escura e efeitos gravitacionais não-newtonianos em galáxias. - Oliveira, Paulo Louzada Castro de (2018)
In this thesis we study the effects of dark matter and non-Newtonian gravity models in the rotation curves of spiral galaxies. Spiral galaxies rotation curve observations are one of the main evidences of the presence of dark matter in the Universe, and at the same time reveal an apparent inconsistency of the standard model of cosmology, whose numerical N-body simulations produce dark matter haloes that are in conflict with these observations. We investigate here firstly, using a large sample of galaxies collected from the literature, wheter some modified gravity models can describe the rotation curves of the galaxies as well as or better as the expectations of the standard model, mainly in the center of the galaxies where the conflict occurs. In the second part we use the same sample of galaxies and develop a new method of analysis which we use to find evidence that even the larger disk galaxies have a conflict, of smaller magnitude, but systematic, between observations and simulations. Finally we investigate also the rotation curve of our galaxy, the Milky Way, in conjuction to another set of observations, the vertival acceleration in the solar vicinity, where our results point to several difficulties of the models alternative to the standard scenario.